Direct Asymmetric Vinylogous Mannich Addition of 3,5-Disubstituted-4-nitroisoxazoles to Isatin-Derived Imines Catalyzed by a Bifunctional Phase-Transfer-Catalyst - Xia, Xuejian; Zhu, Qiongqiong; Wang, Jing; Chen, Jie; Cao, Weiguo; Zhu, Bo; Wu, Xiaoyu (Journal of organic chemistry, 2018)
Asymmetric Mannich-type addition of 3,5-disubstituted-4-nitroisoxazoles to isatin-derived Boc-protected imines has been realized by using 0.01 equiv of amide phosphonium salt as a phase transfer catalyst. Our current methodology allows for the formation of 3-isoxazolylmethyl-substituted 3-aminooxindoles in excellent yields with good to excellent enantioselectivities. The practical value of this methodology was exemplified by a gram-scale synthesis of 5an, a key intermediate for the formal synthesis (+)-AG-041R.